Keanekaragaman dan Kemelimpahan Tumbuhan Paku di Cagar Alam Donoloyo sebagai Bahan Pengembangan Multimedia Interaktif Biologi di SMA - Fitria Nur Hasanah (Journal of Biology Learning, 2020)
This study aims 1) to determine the index of species abundance, characteristics, morphology of ferns in the nature reservearea of Donoloyo, Watusomo, slogohimo 2) to obtain an alternative source of learning biology in high school about the abundance of ferns based on interactive multimedia in the form CD 3) to find out the multimedia validation of interactive learning biology of ferns. This research method is descriptive quantitative exploration, the instrument used is a direct observation technique with the quadrat method and validation sheet. The results of the study showed that in the Donoloyo nature reserve, 12 species of ferns were found in 2 classes and 5 families which showed in the medium category. Observations of ferns are used as learning resources in the form of interactive multimedia learning. The quality of interactive media assessed by 3 validators namely material experts, media experts, and biology teacher get a percentage >80% (very valid) interactive multimedia is ready to be used as a learning media for biology in high school.